Evaluation of the activity of hen eggshell graft in experimentally induced mandibular defects in rabbits: pilot study - Al Anashar, Ahmad; Daoud, Ali (International Journal of Research in Medical Sciences, 2019)
Background: For the treatment of the cranial and maxillofacial bone defects autogenic and/or allogenic bone grafts and alloplastic materials have been used for a long time. In the last decade, avian eggshell powder has been suggested as a bone substitute candidate in reconstructive surgery. The purpose of this study was to investigate the beneficial effects of particulate hen eggshell grafting on the healing of experimentally induced mandibular defects. Methods: The study was conducted on 10 adult local rabbits. Two cavities of 4mm diameter have been created in the lateral surface of the mandible. One of the cavities was filled with particulate hen eggshell graft (test one), while the other hole was left for normal healing (control one). On the 8 weeks, the rabbits have been sacrificed and defective regions have been extracted. Results: All animals showed normal wound healing. No foreign body reaction was observed, hen eggshell grafts were resorbed, integrated with bone at 8 weeks. There were no differences between control and chicken eggshell groups in new bone formation. At 8 weeks, histological analysis of specimens showed different amounts of woven bone contained osteocytes and covered by lining of osteoblasts. Conclusions: Within the limitations of this study, it was concluded that hen eggshell powder is a worth-while bone substitute because it is a safe, cheap, and easily available material.